Direct and indirect savings from parallel imports in Sweden - David Granlund (Health Economics Review, 2022)
Background: The aim was: i) to quantify the direct and indirect savings from parallel imports in Sweden during a period when sellers were forbidden from giving discounts to pharmacies, and ii) to study if the efects of competition from parallel imports on list prices became smaller in absolute size when sellers were allowed to give discounts to pharmacies. Methods: We analyzed the monthly prices for 3068 products during 61months when discounts were forbidden and for 2504 products during 84months when discounts were allowed. The price efects were estimated using dynamic models that rendered lagged numbers of competitors into valid and strong instruments for the current values. Results: When discounts were forbidden, parallel imports had a market share of 16% and were on average 9% cheaper than locally sourced drugs, which yielded a direct saving of 231 million Swedish kronor (SEK) (24 million EUR) per year. Also, parallel imports reduced the prices of products with the same substance by, on average, 6% in the long-term, which yielded indirect savings of 421 million SEK (44 million EUR) per year. In total, parallel imports reduced the cost for on-patent pharmaceuticals by 4%. When discounts were allowed, the average gap in list price between parallel imports and locally sourced products was reduced to 0.8%, and the list prices of locally sourced products were no longer signifcantly afected by competition from parallel imports. Conclusion: When discounts were allowed, the savings of parallel imports through lower list prices were replaced by savings of pharmacies through secret discounts.
Keywords: 330; Brand-name drugs; Parallel trade; Pharmaceutical industry; Pharmacies; Price competition